The Implementation of Student Worksheet Based on STEM (Science, Technology, Engineering, Mathematics) and Local Wisdom to Improve of Critical Thinking Ability of Fourth Grade Students - Prasadi, Anggi Hary; Wiyanto, Wiyanto; Suharini, Erni (Universitas Negeri Semarang, 2020)
The aim of this research is to analyze the effectiveness of students worksheet to improve of critical thinking ability of fourth grade student’s of SD N 5 Parakan Kauman based on STEM (Science, Technology, Engineering, Mathematics) and local wisdom. This research adopt the procedure of research and development that oriented in 4D model (Define, Design, Developed, and Disseminate). The research design used was one groups pretest-posttest design with the member of subject were 24 students. The research instrument used observation sheet, interview sheet, validity test, written test (pretest and posttest), and also questionnaire. The result of the research showed that students worksheet included in the effective enough category, which based on the calculation of N-Gain score was 62.7809 or 62.8 %, with a minimum score is 57.14 % and a maximum score 66.67 %. These scores showed the improvement of student thinking in solving problem aspect, with good and very good categories. The result of the teacher respondent is 67, it is in interesting category and the student respondent got 84 in average score, it is in very interesting category. It can be concluded that the implementation of student worksheet in STEM basic and local wisdom can be implemented in teaching learning activities, it also improve the ability of students’ critical thinking.